Phylogenetic of red snapper (Lutjanidae) in Yapen Island Waters, Papua, Indonesia - Ridwan Sala; Aradea Bujana Kusuma; Bayu Pranata (Society for Indonesian Biodiversity, 2023)
Abstract. Sala R, Kusuma AB, Pranata B. 2022. Phylogenetic of red snapper (Lutjanidae) in Yapen Island Waters, Papua, Indonesia. Biodiversitas 23: 6428-6436. Red snappers are an economically valuable fishery resource. Most of these snapper species are inhabitants of coral reef ecosystems. A variety of red snapper species can be found in the northern waters of Papua, particularly in the Yapen Regency. However, information regarding the biological and ecological aspects of these fish is virtually unavailable. On the other hand, the utilization intensity of red snapper as a source of community income continues to increase. By using DNA barcode sequences, this study attempted to examine species diversity and relationships among Lutjanidae family species. The study was carried out from June to August 2022 in the waters of Yapen Regency by taking fish samples from the fish caught by local hand-lining fishers. Red snapper samples were identified morphologically and molecularly. According to molecular analyses, it was identified nine red snapper species from the genera of Lutjanus, Aphareus and Pristipomoides. The morphological characteristics of the species from the genus of Aphareus are similar to those from the genus of Pristipomoides yet different from those of the species from the genus of Lutjanus. The phylogenetic tree consisted of four clades with significant bootstrap values ranging from 98 to 99%. Clades 1, 2 and 3 comprise the species from the genus of Lutjanus, while clade 4 contains species from the genera of Aphareus and Pristipomoides. The greatest genetic distance was found between Lutjanus fulvus and Pristipomoides multidens, while the smallest genetic distance was found between Lutjanus vitta and Lutjanus ehrenbergii. Based on the study results, some management implications are discussed. For example, information on species biodiversity maps is needed to determine the target stock of a managed species so that management objectives are more focused on the species level and not on the genus or family level.